Życie jak scenariusz. Na marginesie książki (Nie)zapomniani dokumentaliści - Hučková, Jadwiga (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The book (Un)forgotten documentalists, edited by Katarzyna Mąka-Malatyńska and Jolanta Lemann-Zajiček (2020) is a significant achievement in research on Polish documentary film. The review of the collective work, consisting of ten texts preceded by an introduction, becomes the starting point for discussions with selected authors and reflection on the problem of the absence of significant documentary filmmakers in the history of the film. Entire currents are also forgotten, such as a film about art, represented by four out of nine documentary filmmakers discussed in the book. The meanders of life and creativity can be instructive for contemporary documentary filmmakers.